Pengaruh Promosi Dan Saluran Distribusi Terhadap Peningkatkan Volume Penjualan Pada Toko Sablon Baju Jejak 7 Kaos Di Maccini Raya Kota Makassar - Yusril, Muh.; Romadhoni, Buyung; Aulia, Aulia (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of promotions and distribution channels on increasing sales volume at the Jejak 7 Kaos Clothing Screen Printing Shop in Maccini Raya, Makassar City. This study uses a quantitative approach by distributing questionnaires to 100 respondents and analyzing the data using multiple linear regression. The variables studied consist of promotions (X1), distribution channels (X2), and sales volume (Y). The results show that both promotions have a positive and significant effect on increasing sales volume. Based on a significance value of 0.000, out of 0.05, and a regression coefficient of 0.307. It can be concluded that the better the promotion received, the increase in sales volume at the Jejak 7 Kaos Clothing Screen Printing Shop in Maccini Raya, Makassar City. Distribution channels have a positive and significant effect on increasing sales volume. This is evidenced by a significance value of 0.000, out of 0.05 and a regression coefficient of 0.596. The better the distribution channels provided, the more sales volume will increase.